Power System Stability: Modelling, analysis and control - Sallam, Abdelhay A.; Malik, Om P. (IET power and energy series, 2015)
To ensure stable operation of a power system, it is necessary to analyse the power system performance under various operating conditions. Analysis includes studies such as power flow and both steady-state and transient stability. To perform such studies requires knowledge about the models used to represent the various components that constitute an integrated power system. In situations where there is a risk of loss of stability, it is necessary to apply controls that can ensure stable and uninterrupted supply of electricity following a disturbance. The subject of stability thus encompasses modelling, computation of load flow in the transmission grid, stability analysis under both steady-state and disturbed conditions, and appropriate controls to enhance stability. All these topics are covered in this book, providing a comprehensive treatment of the overall subject of stability of power systems. Topics covered include modelling of the synchronous machine; the synchronous machine connected to power systems; modelling of transformers, transmission lines and loads; power flow analysis; optimal power flow; small signal stability; transient stability; transient energy function methods; artificial intelligent techniques; power system stabilizers; series compensation; shunt compensation; compensation devices; and recent technologies. The subject matter is covered at a level that is suitable for students, scientists and engineers involved in the study, design, analysis and control of power systems.